Comparative analysis of fodder legumes in Murmansk Province - I. V Mikhailova; A. B. Khvostova; L. L. Malyshev (Труды по прикладной ботанике, генетике и селекции)
Background. Dairy farming is one of the main segments in the agricultural sector of Murmansk Province. Expanding the range of cultivated legume fodder crops and their cultivars is one of the ways to comprehensively solve the problem of feed in the Kola Peninsula. Introduction of perennial legumes into the feed production practice will reduce the production cost of feeds and improve their quality.Materials and methods. Fodder galega, variable and yellow alfalfa (2005–2009), bird’s-foot trefoil (2006–2007), and sweet clover (2007–2008) were studied at the Polar Experiment Station of VIR. Weather conditions during the years of study differed in temperature and water regimes. Observations and records were made according to VIR’s guidelines. Statistical data processing included the calculation of the main variation parameters and the construction of a generalized linear model of the variance structure.Results. The data are presented on the study of the collection of four perennial fodder legumes in Murmansk Province, Russia, in 2005–2009. Alfalfa surpassed fodder galega, sweet clover and bird’s-foot trefoil in winter hardiness, height and bushiness, showed medium leafiness, and (for the entire study cycle) had low air-dry mass yield. Biennial bicarpic sweet clover stood out for its air-dry mass yield on average per year, had medium height and foliage, but low winter hardiness and bushiness. Bird’sfoot trefoil was significantly inferior to the rest of the studied crops in all agronomic characteristics. Galega had the highest leafiness; in winter hardiness, bushiness and plant height it was slightly inferior to alfalfa, and in yield to white clover. Seeds under the conditions of Murmansk Province can be obtained only from galega accessions.Conclusion. According to a set of agronomic characters, the most promising crop is fodder galega, especially its adapted naturalized accessions selected in 1991–1993.